ANALISIS KUALITAS PELAYANAN MENGGUNAKAN METODE SERVICE QUALITY (SERVQUAL) DAN QUALITY FUNCTION DEPLOYMENT (QFD) DI PT.XYZ - Mega Silvya Tuarissa (2021)
This research was conducted to analyze the quality of services provided by PT. XYZ to every consumer. The purpose of this research is to obtain effective methods for the company in its efforts to improve the quality of services that previously existed in PT. Xyz. In this research, the analysis method used is the integration between Servqual (Service Quality) and QFD (Quality Function Deployment) method modeled into the House of Quality form. In this study, there are 5 Variables (Tangibles, Reliability, Responsiveness, Assurance, Empathy) and 23 attributes designed in analyzing the quality of service in PT. XYZ. Based on the results of this research, it is known that the integration between the two methods is quite effective to analyze the quality of services in PT. XYZ. Besides, from the integration of these two methods, it is known that the service variables that should be prioritized to be improved and improved are the variables "reliability" and for service attributes that should be prioritized to be improved and improved is the 5th attribute "Time of delivery of goods on time" this is seen from the highest GAP weight value with a value of -2.56 therefore PT. XYZ must be able to meet the Time of Delivery of Goods on time. Besides, through the integration of the Service Quality method and QFD method, it is obtained that technical steps need to be done and prioritized to improve and improve the quality of service in PT. XYZ is with "Fast and Clear Service Time Response" this is seen from the Relative Importance value of the highest value weight with a value of 0.205.